New interfaces for a connection by adherence in composite steel-concrete structures - Brasil, Lisarb Henneh (2019)
The technical and economic development of structural alternatives in building construction is a continuous demand. Despite the large number of studies conducted each year, few are dedicated to establishing rigid methodological criteria in order to assess their relevance to the progress of science. Thus, the purpose of a systematic review (SR) may be to discuss data, opinions or practices, provide a survey of previous publications, critique the current work, or make summary projections about future discoveries. In this way, this paper presents a SR related of the structural behavior of Connections by Adherence, aiming to discuss concepts, major findings and research methods employed, which allowed us to infer that the connectors present sufficient shear resistance and ductility so that it can be applied to several types of composite structures, mainly in buildings construction. Furthermore, experimentally evaluates the applicability of connection by adherence between steel and concrete in the context of ribbed slabs. For this purpose, Push-out specimens were fabricated and performed in accordance with Eurocode-4 requirements, where the connection behavior is analyzed in terms of its load-slip relation and the failure modes are identified. All the results allow to induce that the Connector by Adherence made with checkered steel plate is appropriate to use in composite structures, as it certainly exhibited satisfactory performance in terms of ultimate shear resistance and ductility.